Defining and Exploring Broadband Connections and Education Solutions in Canada’s North - Soanes-White, Tammy (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2022)
The use of technology and need for connection across distance permeates all education environments; nowhere is this more important than in Canada’s Northwest Territories. Broadband and telecommunications issues within the Northwest Territories are complex due to its vast geographical area and community dispersion, making connectivity and accessibility inconsistent. Due to these conditions, the North relies on a variety of broadband solutions to improve Internet speeds and access to education at a distance. This paper analyzes the impacts that broadband capacity and Internet access have on remote education by examining geographic information system data, which offers a framework that connects spatial and temporal data to analyse accessibility of remote education. Characteristics such as spatial location of communities, infrastructure (road systems), and the overlay of various broadband options will illustrate constraints and (dis)connectivity in various regions and inform readers about the complexity of remote connections. Analysis of current upload and download speeds from various regions and their impact on access to education supports geospatial data and analysis that the digital divide in remote regions of Canada has increased and is widening. Improving equitable access to postsecondary education will require a greater reliance on technology-enabled practices to improve learning opportunities.